Confident leaders by design : an essential guide to confidence creation - Baker, Chris (Routledge, 2026)
Do you feel confident at work? Are there times when you lack confidence but can't show it? The role of confidence in successful leadership is both significant and undisputed and yet organisations are full of leaders and teams who don't have as much as they want and, even worse, are not doing anything about it.Attempts to develop confidence are usually confined to empty affirmations and vanilla-flavoured self-help books. In contrast, this book provides an evidence-based code that outlines the steps we can all take to positively shift our confidence and that of our teams. Confident Leaders by Design is for leaders at all levels looking for a rigorous yet accessible approach to confidence development. Through research and fascinating anecdotes it reveals the surprising secrets to supercharging leadership potential through confidence creation.Alongside the theory, readers will practically locate their confidence sweet spot and explore activities like sludge audits, confidence curves and self-efficacy circles which will help them to immediately start growing confidence in themselves and their teams.